1976
DOI: 10.1021/bi00658a030
|View full text |Cite
|
Sign up to set email alerts
|

The "phosphoryl-enzyme" from phosphoglycerate kinase. Appendix: Crystalline 3-phospho-D-glycerate kinase from horse muscle

Abstract: The "phosphoryl-enzyme" prepared from phosphoglycerate kinase and adenosine 5'-triphosphate in the presence of an adenosine 5'-diphosphate trap is shown to contain stoichiometric amounts of 3-phosphoglycerate. This "phosphoryl-enzyme" is chemically competent, but is probably just a tight complex between 1,3-bisphosphoglycerate and the enzyme. The two partial exchange reactions (between adenosine 5'-diphosphate, and adenosine 5'-triphosphate, and between 3-phosphoglycerate and 1,3-bisphosphoglycerate) can both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…experiments showed that similar enzyme preparations contained significant amounts of organic phosphate (single phosphoryl peak) before, but not after, exhaustive dialysis. This correlates with the finding of Johnson et al (1976) that preparations of yeast PGK can contain contaminating amounts of a triose substrate. Conroy et al (1981) have since shown that active site arginine residues react only slowly with phenylglyoxal unless PGK is first incubated with the enzyme and cofactors which are required to convert 3-PGA to glyceraldehyde-3-phosphate.…”
Section: -Pga Bindingsupporting
confidence: 88%
See 1 more Smart Citation
“…experiments showed that similar enzyme preparations contained significant amounts of organic phosphate (single phosphoryl peak) before, but not after, exhaustive dialysis. This correlates with the finding of Johnson et al (1976) that preparations of yeast PGK can contain contaminating amounts of a triose substrate. Conroy et al (1981) have since shown that active site arginine residues react only slowly with phenylglyoxal unless PGK is first incubated with the enzyme and cofactors which are required to convert 3-PGA to glyceraldehyde-3-phosphate.…”
Section: -Pga Bindingsupporting
confidence: 88%
“…Although both enzymes bind 3-PGA the reactions catalysed are very different. The mutase forms a phosphoryl intermediate (Rose, 1980) whereas the kinase does not (Johnson et al, 1976).…”
Section: Molecular Structurementioning
confidence: 99%
“…Other nucleoside-metabolizing enzymes have not exhibited a similar preference for Ldeoxynucleoside analog diphosphates, and the property is unique to PGK. Human PGK (ϳ46 kDa) is a glycolytic enzyme that catalyzes the conversion of 1,3-biphosphoglycerate to 3-phosphoglycerate and during the process generates one molecule of ATP (17). The reaction is reversible.…”
mentioning
confidence: 99%
“…Also, the isoelectric point of the renatured enzyme focused in 3M-urea was identical with that of native enzyme, also focused in 3 M-urea. Such an anion could be the substrate for the enzyme, 1,3-diphosphoglycerate, which Johnson et al (1975Johnson et al ( , 1976) have shown to be tightly bound to the enzyme.…”
Section: Discussionmentioning
confidence: 99%